Exit programmes for female jihadists: a proposal for conducting realistic evaluation of the Dutch approach - Gielen, Amy-Jane (2018)
Europe has seen an increase of women joining or sympathizing with the terrorist organization ISIS. These women are often considered victims and passive agents, but their threat should not be underestimated. Effective counter-measures are essential, especially now the so-called caliphate is in decline and many females want to return home. Exit programmes to deradicalize, disengage, reintegrate or rehabilitate are often part of a broader programme to prevent and counter violent extremism (CVE). Little is known about the effectiveness of such exit programmes, in particular in relation to female violent extremism. Drawing on municipal exit programmes in the Netherlands as a case study, the article researches how realistic evaluation can be used to measure the effectiveness of exit programmes. It also shows that the realistic evaluation method is beneficial for further theory development on the phenomenon of female violent extremism. - Reproduced.
Keywords: Extremism; Jihadists; Terrorism; Women in terrorism